Mitochondrial Dynamics, Mitophagy, and Mitochondria–Endoplasmic Reticulum Contact Sites Crosstalk Under Hypoxia - Wang, Shuying; Tan, Jin; Miao, Yuyang; Zhang, Qiang (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are double membrane organelles within eukaryotic cells, which act as cellular power houses, dependent on the continued availability of oxygen. Nevertheless, under hypoxia, the disordered metabolism disturbs the homeostatic status of mitochondrial network, which leads to dysfunctions of mitochondria, producing a large amount of reactive oxygen species that cause further damage to the cell. Compelling evidence have shown that the disruption of mitochondrial homeostasis under hypoxia is linked to a wide spectrum of human diseases, including obstructive sleep apnoea, diabetes, cancer and cardiovascular disorders. As such, the quality-control mechanism is highly required to maintain a health population of mitochondria to fit cell needs. Mitochondrial dynamics play a central role in monitoring the condition of mitochondrial quality. The fission–fusion cycles are regulated to attain a dynamic equilibrium under normal conditions, however, it will be disrupted under hypoxia, resulting in mitochondrial fission and selective removal of impaired mitochondria through mitophagy. Current researches suggest that the molecular machinery underlying these well-orchestrated processes are coordinated at mitochondria–endoplasmic reticulum contact sites. Here, we establish a holistic understanding of how mitochondrial dynamics and mitophagy are regulated at mitochondria–endoplasmic reticulum contact sites under hypoxia.